Parental socioeconomic status and adolescent health in Japan - Shohei Okamoto (Nature Portfolio, 2021)
Abstract There is no consensus on which parental socioeconomic indicators should be used to define adolescents’ socioeconomic status (SES). Utilising the data for 3154 parent-adolescent pairs obtained from the sample of the Survey of Lifestyle Value of Parents and Children 2011 conducted by the Cabinet Office in Japan, the associations between adolescent’s subjective economic status, parental SES (i.e. education, occupation, and household income), and child health-related outcomes (i.e. self-rated health, dietary and oral health behaviours) were analysed using multilevel mixed-effects ordered logistic regression to investigate heterogeneity in these relationships across SES indicators and health outcome measures. Results demonstrated that income was the strongest predictor of adolescent health outcomes, suggesting that adolescents in the middle- or high-income groups tended to report better health status compared to the low-income group, have a higher frequency of having breakfast, and more likely to regularly brush their teeth by 24% (OR 1.24, 95% CI [1.06–1.46]) to 66% (OR 1.66, 95% CI [1.30–2.12]). Parental education was also related to child health-related behaviours, with higher levels of habitual healthy behaviours being observed in the middle- and high-education groups than in the low-education group by 15% (OR 1.15, 95% CI [1.01–1.32]) to 63% (OR 1.63, 95% CI [1.31–2.03]). Future studies regarding health disparities among children/adolescents should carefully choose an SES indicator, taking multiple pathways between each SES indicator and health/health behaviours into consideration.